MMP-9 as a Candidate Marker of Response to BRAF Inhibitors in Melanoma Patients With BRAFV600E Mutation Detected in Circulating-Free DNA - Salemi, Rossella; Falzone, Luca; Madonna, Gabriele; Polesel, Jerry; Cinà, Diana; Mallardo, Domenico; Ascierto, Paolo A.; Libra, Massimo; Candido, Saverio (Frontiers in Pharmacology, 2018)
The BRAFV600E mutation is associated with melanoma development and its detection in circulating-free DNA cannot be observed in all melanoma patients harboring this mutation in tumor specimens. Beside the circulating-free DNA BRAFV600E mutation, other markers of therapeutic response should be identified. Matrix metalloproteinase-9 (MMP-9) could be one of them as its role as indicator of invasiveness in melanoma have been explored. In this study, MMP-9 was evaluated in melanoma cells after treatment with dabrafenib. In vitro data were validated in 26 melanoma patients, of which 14 treated with BRAF inhibitor alone and 12 treated with both BRAF and MEK inhibitors, by ELISA assay and droplet digital PCR for measuring MMP-9 serum levels and circulating-free DNA BRAFV600E mutation, respectively. Statistical analyses were performed to evaluate the prognostic significance of MMP-9, progression-free survival (PFS) and overall survival (OS) according to the BRAFV600E mutation and MMP-9 levels. The performed analyses showed that MMP-9 and pEKR1-2 were statistically down-regulated in melanoma cells after treatment with dabrafenib. Circulating-free DNA BRAFV600E mutation was detected in 11 out of 26 melanoma patients showing higher levels of MMP-9 compared to those with undetectable BRAFV600E mutation. Furthermore, higher levels of MMP-9 and circulating-free DNA BRAFV600E mutation were associated with lower PFS and OS. Finally, the monitoring of therapy showed that MMP-9 significantly decreased at T1 and T2, but not at T-last, for the patients with detectable circulating-free DNA BRAFV600E mutation. In conclusion, high levels of MMP-9 and circulating-free DNA BRAFV600E mutation are associated with poor PFS and OS. MMP-9 may represent a promising indicator of response to BRAF inhibitors in combination with the detection of BRAFV600E mutation.